Entrepreneurial Intention and Delayed Job Satisfaction From the Perspective of Emotional Interaction: The Mediating of Psychological Capital - Na, Boxiang; Ahmad, Noor Hazlina; Zhang, Chenxiao; Han, Yan (Frontiers in Psychology, 2022)
The COVID-19 pandemic has exacerbated the labor shortage and promoting entrepreneurship to spur job creation is one of the most effective strategies to address this problem. Entrepreneurs must lengthen their employment or start-up cycles as a result of COVID-19 normalization. Consequently, the impact of career willingness to delay satisfaction on entrepreneurial ambition is investigated in this research. The findings show that students with a high level of career delayed contentment have a higher level of entrepreneurial intention, implying that career delayed contentment intention influences entrepreneurial intention positively. Psychological capital serves as a moderator in this process, increasing the influence of job delayed satisfaction on entrepreneurial intention by strengthening psychological capital. The major components that determine psychological capital are self-efficacy, hope, optimism, and flexibility. This study combines the willingness to wait satisfaction with the willingness to start a business, providing a valuable reference for reducing the work condition caused by the COVID-19 epidemic.